THE EFFECT OF REGIONAL FINANCIAL ACCOUNTING SYSTEM AND INTERNAL CONTROL SYSTEM ON FINANCIAL PERFORMANCE OF MAKASSAR CITY GOVERNMENT - Abdul Rival; Marwah Yusuf; Sufiati Sufiati (Contemporary Journal on Business and Accounting, 2022)
Purpose – This study aims to determine the effect of the regional financial accounting system and internal control system on the financial performance of the Makassar city government. Design/methodology/approach – Methods of data analysis using multiple linear regression analysis method. Findings – The results showed that the regional financial accounting system and internal control system simultaneously had a positive and significant effect on the financial performance of the Makassar city government, the regional financial accounting system partially had a positive and significant effect on the Makassar city government's financial performance, and the internal control system partially had a positive effect. and significant to the financial performance of the Makassar city government. Originality – The population in this study were all regional organizations totaling 52 OPD. Keywords: Regional Financial Accounting System, Internal Control System, Government Financial Performance Paper Type Research Result